Computational characterization of turbulent flow in a microfluidic actuator (2022)
In this contribution, an unsteady numerical simulation of the flow in a microfluidic oscillator has been performed. The transient turbulent flow inside the device is described by the Unsteady Reynolds Averaged Navier–Stokes equations (URANS) coupled with proper turbulence models. The main characteristics of the complex fluid flow inside the device along one oscillation cycle was analyzed in detail, including not only velocity contours but also the pressure and turbulent kinetic energy fields. As a result, two-dimensional simulations provided good estimations of the operating frequency of the fluidic actuator when compared with experimental measurements in a range of Reynolds numbers. Moreover, with the objective of altering the operating frequency of the apparatus and, in order to adapt it to different applications, geometrical modifications of the feedback channels were proposed and evaluated. Finally, a fully three-dimensional simulation was carried out, which allowed for the identification of intricate coherent structures revealing the complexity of the turbulent flow dynamics inside the fluidic oscillator